2023
DOI: 10.1001/jamapsychiatry.2023.0019
|View full text |Cite
|
Sign up to set email alerts
|

State Cannabis Legalization and Cannabis Use Disorder in the US Veterans Health Administration, 2005 to 2019

Abstract: ImportanceCannabis use disorder (CUD) is increasing among US adults. Few national studies have addressed the role of medical cannabis laws (MCLs) and recreational cannabis laws (RCLs) in these increases, particularly in patient populations with high rates of CUD risk factors.ObjectiveTo quantify the role of MCL and RCL enactment in the increases in diagnosed CUD prevalence among Veterans Health Administration (VHA) patients from 2005 to 2019.Design, Setting, and ParticipantsStaggered-adoption difference-in-dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 74 publications
1
23
0
Order By: Relevance
“…Previous national studies of MCL and RCL found post-enactment increases in the prevalence of self-reported use 2,9,10 and also in clinical diagnosis for cannabis use disorder (CUD) diagnoses in VHA patients, diagnoses that cannot be made without self-reported cannabis use. 8 Cannabis legalization could reduce concerns about disclosing cannabis use in surveys and clinical settings, potentially leading to artifactual findings on prevalence increases and MCL and RCL effects. An earlier VHA study showed increases in CUD diagnoses associated with MCL and RCL enactment from 2005 to 2019 among the overall VHA patient population 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous national studies of MCL and RCL found post-enactment increases in the prevalence of self-reported use 2,9,10 and also in clinical diagnosis for cannabis use disorder (CUD) diagnoses in VHA patients, diagnoses that cannot be made without self-reported cannabis use. 8 Cannabis legalization could reduce concerns about disclosing cannabis use in surveys and clinical settings, potentially leading to artifactual findings on prevalence increases and MCL and RCL effects. An earlier VHA study showed increases in CUD diagnoses associated with MCL and RCL enactment from 2005 to 2019 among the overall VHA patient population 8 .…”
Section: Discussionmentioning
confidence: 99%
“…8 Cannabis legalization could reduce concerns about disclosing cannabis use in surveys and clinical settings, potentially leading to artifactual findings on prevalence increases and MCL and RCL effects. An earlier VHA study showed increases in CUD diagnoses associated with MCL and RCL enactment from 2005 to 2019 among the overall VHA patient population 8 . Since our UDS data do not rely on self-report or clinical attention to cannabis use disorder symptoms, the present study provides an important new source of data to understand the effects of MCL and RCL policies.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis is now legal for medical use in at least 37 states and the District of Columbia (DC) and for recreational use in 21 states and DC. 1 With the gradual expansion of legal access to cannabis over the past 2 decades, the prevalence of cannabis use has increased in both the general population and veterans. 1 Although the reported use of cannabis within the past year among US military personnel remains low at less than 1%, 2 this low rate is likely attributable to regulations that prohibit its use, with severe penalties (eg, administrative separation and potentially other-than-honorable discharge with reduced benefits) for military personnel.…”
mentioning
confidence: 99%
“…1 With the gradual expansion of legal access to cannabis over the past 2 decades, the prevalence of cannabis use has increased in both the general population and veterans. 1 Although the reported use of cannabis within the past year among US military personnel remains low at less than 1%, 2 this low rate is likely attributable to regulations that prohibit its use, with severe penalties (eg, administrative separation and potentially other-than-honorable discharge with reduced benefits) for military personnel.While the use of nonprescribed cannabis products is uncommon and illegal in the military, 3 cannabinoids are approved by the US Food and Drug Administration and can be legally prescribed to military personnel and veterans in clinical settings. Dronabinol, in particular, is occasionally prescribed to military personnel off-label to treat pain or symptoms of posttraumatic stress disorder (PTSD).…”
mentioning
confidence: 99%
See 1 more Smart Citation